EAP Course Design: A Need Analysis on Digital Business Students in Business Technology Institute of Riau (ITBR) - Erna Nawir; Robeeyah Bueraheng; Widia Yunita; Desna Fauziah; Wenny Elsara (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
This research helps determine the necessary requirements to strengthen a design of an English for Academic Purposes (EAP) course in the context of English as a foreign language, particularly in Indonesia, especially despite its marginal status in higher education curricula by exploring EAP student needs, specifically in the Digital Business department at the Institute of Digital Business Technology Riau (ITBR). Employing a qualitative descriptive approach, the research utilizes questionnaires and an interview guide to gather data from students, the head, and English instructor in the department in order to identify student needs through 1) target situation analysis, 2) discourse analysis, 3) present situation analysis, 4) learner factor analysis, and 5) teaching factor analysis. The findings reveal that the last four aspects of the needs analysis are evenly distributed, showing a total percentage of 21% of the overall percentage students' needs, indicating that students require authentic materials for the development of their skills and language components, they need proficient language skills, they also require motivation, varied teaching methods and learning environments, and they need appropriate classroom management. In contrast, the target situation analysis accounts for 16% of the overall percentage, mainly due to the differing perceptions between students, department chairs, and teaching staff. In conclusion, students in the Digital Business department have specific needs accompanied by high motivation, which supports their attainment of good communication skills in their field, emphasizing the importance of aligning perceptions regarding the needs in developing an EAP course to achieve EAP learning objectives.